Conversion and Jesuit schooling in Zambia - Carmody, Brendan Patrick. (Studies in Christian Mission, 1992)
This is a socio-historical study of schooling at Chikuni, a Jesuit mission station in Southern Zambia. It includes an examination of the dynamic processes operative at the mission over a 75 year period. During these years, the Jesuits interacted with successive generations of students and converts and with the representatives of successive political regimes, all of which were secular but each willing to use the mission as a means to its own ends. For many years Chikuni was the major representative of the Catholic church in southern Zambia. The emergence of a Catholic community is of its making. As its educational role expanded it also helped to form many who became leaders in post-independence Zambia. Though the Jesuits had not planned a political revolution, unwittingly they helped to bring one about. While the study identifies some of the difficulties connected with running a denominational school in present day Zambia, it argues for a more pivotal positioning of conversion as a socio-personal religious phenomenon in the curriculum if the mission school is to continue to be an effective agent of transformation.